Optimization of Chitosan and Cellulose Acetate Phthalate Controlled Delivery of Methylprednisolone for Treatment of Inflammatory Bowel Disease - Swati Jagdale; Apoorva Chandekar (Tabriz University of Medical Sciences, 2017)
Purpose: Inflammatory bowel disease (IBD) is a chronic, relapsing and often life-long disorder. The best way to tackle IBD is to develop a site targeted drug delivery. Methylprednisolone is a potent anti-inflammatory steroid. The relative potency of methylprednisolone to hydrocortisone is at least four is to one. The aim of the present research was to develop a colon targeted drug delivery for treatment of IBD. Methods: Compression coated drug delivery system was designed and optimised. Core tablet contained drug, croscarmellose sodium (CCS-superdisintegrant), avicel (binder) and dicalcium phosphate (diluent). Design of experiment with 32 factorial design was applied for optimization of compression coated delivery. Chitosan and cellulose acetate phthalate were chosen as independent variables. Swelling index, hardness and % drug release were dependant variables. Results: Core tablet (C5 batch) containing 2.15% CCS showed disintegration in less than 10sec. FTIR, UV and DSC study had shown absence of any significant physical and chemical interaction between drug and polymers. F8 was found to be optimised formulation. F8 contained 35% chitosan and 17.5% cellulose acetate phthalate. It showed drug release of 86.3% ± 6.1%, hardness 6.5 ± 1.5 and lag time 7 hrs. Simulated media drug release was 97.51 ± 8.6% with 7.5 hrs lag time. The results confirmed that the lag time was highly affected by the coating of the polymers as well as the concentration of the superdisintegrant used in core tablet. Conclusion: In-vitro and in-vivo results confirmed a potential colon targeted drug therapy for treatment of IBD.